Protocol for rapid assessment of the efficacy of novel Wnt inhibitors using zebrafish models - Haney, Meghan G. (STAR Protoc, 2021)
Dysregulation of Wnt signaling is a hallmark of many cancers, and the development of effective, non-toxic small-molecule Wnt inhibitors is desirable. Off-target toxicities of new compounds are typically tested in mouse models, which is both costly and time consuming. Here, we present a rapid and inexpensive protocol to determine the in vivo toxicity and efficacy of novel Wnt inhibitors in zebrafish using a combination of a fluorescence reporter assay as well as eye rescue and fin regeneration assays. These experiments are completed within 1 week to rapidly narrow drug candidates before moving to more expensive pre-clinical testing. For complete details on the use and execution of this protocol, please refer to Zhang et al. (2020).